IMPLEMENTASI TEKNOLOGI TELEKOMUNIKASI DALAM SISTEM INFORMASI AKUNTANSI UNTUK PERTUKARAN DATA DI LINGKUNGAN BISNIS GLOBAL - Usman Bakar (Jurnal Telaah dan Riset Akuntansi, 2009)
This paper illustrates the importance the telecommunication technology as an effort to improve  data interchange in to accounting information systems in global business. The corporates will use a information system  to provide data and/or information, improves accuracy, efficiency, and effectiveness of customer payments in the global business. The Telecommunication Technology can be done in five ways: Autometic Teller Machine, telecoferencing, workgroup computing, telecommuting, and electronic data interchange..The accounting information systems in to global businees cycles needed telecommunication technology equipment especially for electronically  transferring information between organizations and across business processesThe electronically  transferring information effects on value chain activities ect: the improves the purchasing activity by making it easier for a business to identify potential suppliers and to compare prices;  the efficiency and effectiveness of customer payments; the efficiency and effectiveness of the human resource support activity; and the efficiency of internal operations.The accounting information sistem roles to be able to integrate information of different types and from different sources, as well as in to global busness.      Keywords: Telecommunication Technology, Electronic Data Interchange, and Accounting Information Systems